The fentanyl phase of the opioid epidemic in Cuyahoga County, Ohio, United States. Issue 3 (4th January 2021) - Deo, Vaishali S.; Gilson, Thomas P.; Kaspar, Claire; Singer, Mendel E.
Abstract: Since late 2014, fentanyl has become the major driver of opioid mortality in the United States. However, a descriptive analysis of fentanyl victims is limited. We studied the 2016 fentanyl and heroin overdose deaths and compared them to previously studied heroin‐associated fatalities from 2012 over a wide range of demographic and investigative variables, including overdose scene findings, toxicology results, and prescription drug history. We observed a significant increase in fentanyl‐related deaths ( n = 421, 2016) versus heroin deaths ( n = 160, 2012) but the baseline demographics between both cohorts remained similar. Victims were predominantly of ages 35–64 years (60%–64%), White (83%–85%), and male (73%–76%). 2016 fentanyl decedents were more likely to have naloxone administered upon overdose, and the majority still had a positive prescription history for a controlled substance. Toxicology data showed a decrease in mean morphine and 6‐monoacetylmorphine concentrations when cointoxication with fentanyl occurred. Our study emphasizes the medical examiner's role as a public health data source and bridge between different stakeholders combating the opioid epidemic.